PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP LOYALITAS MEREK SEPEDA POLYGON STRATTOS DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING DI PT INSERA SENA (SURVEI TERHADAP KOMUNITAS POLYGON STRATTOS USER INDONESIA) - Sianipar, Martin Yehezkiel; Lie, Darwin; Butarbutar, Marisi; Julyanthry, Julyanthry (SULTANIST: Jurnal Manajemen dan Keuangan, 2018)
The results of this study can be summarized as follows: 1. The price, product quality, and brand loyalty Polygon Strattos on PT Insera Sena quite well and consumers are still quite satisfied. 2. Results of regression analysis is Å¶(Z) = 17,394 + 0,292X1 + 0,212X2, meaning the price and product quality positively affects consumer satisfaction and simple linear regression result Å¶ = 16,474 + 0,797X(Z). 3. The results of the analysis obtained first correlation r = 0,584 means that there is a moderately correlation between price and product quality with consumer satisfaction and the results of the analysis obtained second correlation r = 0,570 means that there is a moderately correlation between consumer satisfaction with brand loyalty. The hypothesis H0 is rejected, meaning the price and product quality significant positive effect on brand loyalty of Polygon Strattos Bicycle through consumer satisfaction as intervening variable, either simultaneously or partially.The suggestions from this study are 1. that if viewed from the price, the company should give discount to ritel consumer who buy more one unit, 2. concerning product quality, company should pay attention to the color choice bike, 3. consumer satisfaction should improve consumer support especially related to bike information on the website, and 4. at brand loyalty should care about product quality.Â Keywords: Price, Product Quality, Brand Loyalty, and Consumer Satisfaction